INSTITUTIONAL GOVERNANCE IN THE IMPLEMENTATION OF OIL PALM REPLANTING POLICY ON PEATLANDS - Mayarni, Mayarni; Heriyanto, Meyzi; Simanjuntak, Harapan Tua Ricky Freddy; Bedasari, Hafzana; Vani, Resa Vio; Carolina, Minda Putri; Rahmadini, Nurkamila (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Lambung Mangkurat, 2023)
Oil palm is one of the leading plantation commodities and has a strategic role in the national economy. Indragiri Hilir Regency is one of the areas with the fastest-growing oil palm plantations in Riau Province. The area of oil palm plantations owned by People's Plantations (RA) in Indragiri Hilir Regency in 2022 will be 308,197 Ha with a total production of 912,875 tons. The research objective was to determine institutional governance in the implementation of Palm Oil Replanting in the peat hydrological area in the Indragiri Hilir district and the role of governance in its implementation. This study uses a qualitative descriptive method with a relevant literature study approach, using a data analysis technique, namely literature analysis. The results of the study show that the management of the Palm Oil Replanting program in the Indragiri Hilir district has not been maximised because the implementation process is hampered by land status, which raises several challenges for stakeholders. The problem of palm oil governance is not only in the absence of regulations but in policy interventions in the field. Relevant institutional and policy arrangements lead to a balanced and successful implementation of the smallholder palm oil replanting program.